Utility of pulse-oximetry screening in newborns with nonductus-dependent cyanotic congenital heart defects: A reason to alarm? - Balaji Arvind; Anita Saxena; Sivasubramanian Ramakrishnan (Wolters Kluwer Medknow Publications, 2022)
Objectives : We aimed to compare the performance of pulse-oximetry screening in detecting nonductus-dependent cyanotic congenital heart defects (CCHDs). Methods : In a prospective cross-sectional study, we recorded post ductal saturation of neonates (<48 h old) born at a community hospital in northern India. Subsequently, all underwent clinical examination and echocardiogram by a trained cardiologist. A saturation <95% was considered a "failed" screen. Results : Ten neonates were identified to have nonductus-dependent CCHD on echocardiogram, five of whom had passed pulse-oximetry screen. This translated to a sensitivity of 50% (95% confidence interval [CI] 23.7%-76.3%) and a positive predictive value of 0.08 (95% CI 0.03-0.2), both of which were significantly less compared to that in ductus-dependent congenital heart defect. Conclusions : Up to half of the nonductus-dependent CCHD may be missed if screened only using pulse oximetry. Parents should not be reassured regarding the absence of CCHD only based on a "pass" in pulse-oximetry screening.